Network toxicology and molecular docking reveal the potential link between acrylamide exposure and breast cancer - Zhaoda Duan; Chunjiao Yu; Wenjie Yang; Wenhui Wang; Qi Zhang; Qiaoling Ruan; Rui Zhang; Yongfang Zhao; Shan Yan (Scientific Reports)
Abstract Acrylamide (ACR) is a common food and environmental contaminant with potential carcinogenicity, but its molecular role in the development of breast cancer (BC) remains unclear. This study employed a network toxicology and molecular docking strategy to explore the potential association between ACR exposure and BC. Differentially expressed genes were first identified by comparing gene expression profiles between breast cancer and normal tissues. BC-related targets were then screened through integrated analysis of multiple databases and intersected with ACR-associated targets, resulting in 49 shared genes. Protein–protein interaction network construction and MCC algorithm analysis identified 10 core genes. GO and KEGG enrichment analyses revealed that these genes were mainly involved in pathways such as PI3K-Akt signaling, HIF-1 signaling, and ECM–receptor interactions. Molecular docking results suggested that ACR could bind to key targets including EGFR, FN1, JUN, and COL1A1. Molecular dynamics simulations demonstrated that the complexes remained structurally stable throughout the simulation. Pan-cancer and paired sample analyses further confirmed the aberrant expression of core genes in BC, and immunohistochemistry results supported their altered protein levels. These findings suggest that ACR may interfere with BC-related molecular mechanisms through multi-target and multi-pathway interactions, providing theoretical evidence for its potential carcinogenic role and future risk assessment.